Sprint training using sleds and parachutes/Entrenamiento de sprint mediante el uso de trineo y paracaídas - Alexis García Ponce de León; José Enrique Carreño Vega (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The individualized training of specific races with resisted means is an important tool for the improvement of speed. Due to the demand of this capacity for the good performance of baseball players, the objective of this study is to design a sprint training using sled and parachute. A quasi-experiment is planned, with two groups: control and experimental and in two moments: pre-test and post-test. The experimental stage is developed during the pre-season, conformed by a sample of ten subjects with 20.84 years of age and 79 82kg. of average weight. Theoretical methods used were analytical synthetic, inductive-deductive, historical-logical and systemic-structural-functional. The empirical methods were content analysis, observation and measurement. For the measurement of linear speed, the variables analyzed are the 60-yard test and the maximum strength tests of the sled and squat. The results achieved indicated significant improvements in the experimental group in the three tests performed, with % increases equal to 3.48, 7.25 and 7.46 respectively. In addition, it is obtained that there is a high correlation between the maximum strength of the sled and the squat with respect to the weight of the athletes' effort performance, with Pearson coefficients equal to 63.6 % and 62.9 % respectively and for a 95 % of confidence. It is demonstrated that resisted training provides key information in the maximum velocity phase for the improvement of sprint performance in baseball.